Word-problem solving as a function of problem type, situational context and drawing - Vlahović-Štetić, Vesna (Array, 1999)
The purpose of this study was to test the performance of first graders on various types of mathematical addition and subtraction problems with neutral and familiar situational context, as well as with drawing the elements of the task. The experiment was carried out with repeated measures on the same subjects. The data show that compare problems were more difficult for the first grade children than combine problems. Data analysis reveals that the average performance in neutral situational context is somewhat poorer than the one in familiar context but only performance in compare problems is significantly better in familiar situational context. There was no difference in the children's performance with or without drawing task elements. The analysis of the children's errors shows that a "wrong operation" is the most frequent kind of error in all types of problems but it is more usual in the compare than in the combine and change problems. The results of the study are interpreted as congruent to Reusser's model of the word problem solving.